Associations between gender, school socioeconomic status, and cardiorespiratory fitness among elementary and middle school students - Timothy J. Walker; Derek W. Craig; Andjelka Pavlovic; Shelby Thiele; Harold W. Kohl (BMC, 2020)
Abstract Background Schools play an important role in providing access to physical activity opportunities for children. There are common economic and gender disparities in physical activity and health-related fitness among children, which may inform a school's programming needs. The purpose of this study is to gain a better understanding about gender, school-level socioeconomic status, and children's cardiorespiratory fitness. Methods This observational study used 2017-2018 school year data from schools in the Dallas Metropolitan area participating in the Healthy Zone School (HZS) program. Three data sources were integrated: 1) FitnessGram® data, 2) school-level data from the Texas Education Agency, and 3) HZS survey data. Being in the Healthy Fitness Zone (HFZ) for aerobic capacity was the dependent variable, and gender and the percentage of economically disadvantaged students (at the school-level) were key independent variables. Mixed-effects logistic regression models examined associations between dependent and independent variables. Final models were adjusted for age and type of aerobic test. Results There were 67 schools and 15,052 students included in the analysis. When testing main effects, girls had lower odds for being in the HFZ for aerobic capacity than boys (OR = 0.54, CI = 0.47-0.62). Additionally, having a greater percentage of students who were economically disadvantaged was associated with lower odds for being in the HFZ for aerobic capacity (0.98, CI = 0.98-0.99). There was a significant interaction between gender and the percentage of economically disadvantaged students. Results indicated girls had even lower odds (than boys) for being in the HFZ in schools with 90% economically disadvantaged students (OR = 0.44, CI = 0.35-0.55) versus in schools with 15% economically disadvantage students (OR = 0.62, CI = 0.51-0.76). Conclusions Results suggest girls in Healthy Zone Schools have lower odds to meet aerobic capacity fitness standards than boys. Additionally, boys and girls in schools serving a greater percentage of economically disadvantaged students have lower odds to meet aerobic capacity fitness standards. Last, girls have even lower odds of meeting HFZ standard when attending a school serving a greater percentage of economically disadvantaged students. Thus, schools need to provide more programs for girls targeting aerobic physical activity. This is especially important for schools serving a high percentage of low-income students.